An Efficient Voice Based Person Identification System for Secured Communication - Farook, Kadher; Manikandan, S; Basheer, Shakila; Raj, Albert Irudaya (International Journal of Computer Sciences and Engineering, 2018)
Secured Communication is essential due to scalability due to increase number of devices and drastically growing number of people involved in communication. In this paper a voice comparison based communication authentication mechanism is used for providing secured communication. This voice based authentication is used in two different applications like people communication and data retrieval. Before going to speak with people in online their information and their voice is compared and verified from the database and permission will be granted. Similarly according to the voice they can retrieve the data from the data base, where it provides data integrity. Both applications comprise a number of stages such as: (i) Voice, Voice to Text input, (II). Voice Comparison and Pattern Matching. Finally (III). Permission Granted and Data Retrieval (DR) as the output. In order to improve the accuracy and relevancy the proposed data retrieval system, it uses an indexing method called Bag of Words (BOW). BOW is like an index-table which can be referred to store, compare and retrieve the information speedily and accurately. Index-table utilization in DRS improves the accuracy with minimized computational complexity. The proposed DRS is simulated in DOTNET software and the results are compared with the existing system results in order to evaluate the performance.